Report on an Explosion and Fire involving the Motor Vessel Atlantic Duchess at Queen's Dock, Swansea, Glamorganshire on 2nd February, 1951 - Watts, H. E. (His Majesty's Stationary Office, 1951)
REPORT TO THE RIGHT HONOURABLE THE SECRETARY OF STATE FOR THE HOME DEPARTMENT ON THE CIRCUMSTANCES ATTENDING AN EXPLOSION AND FIRE WHICH OCCURRED ON 2ND FEBRUARY. 1951, AT QUEEN'S DOCK SWANSEA, IN THE COUNTY OF GLAMORGANSHIRE, INVOLVING THE MOTOR VESSEL ATLANTIC DUCHESS BY H. E. WATTS H. M. CHIEF INSPECTOR OF EXPLOSIVES
ERAF: A12.P29
Keywords: Fire; explosion; Swansea; ATLANTIC DUCHESS